Analisis Saling-Pengaruh Harga Kopi Indonesia dan Dunia - Budiman Hutabarat (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2006)
EnglishMarket destination of Indonesian coffee remains directed into external markets because domestic consumption per capita of coffee is still very low as well as its rate of growth, while the rate of consumption growth in foreign markets were kept very high and persistently growing. The question is whether or not these coffee markets were integrated and whether or not the prices in the two production centers in Indonesia were also integrated. To formulate policies that could be used to empower coffee farmers and manage their production, information and data pertaining to integration and causal relationship among these markets are badly needed. This paper aims (a) to evaluate the growth and variation of prices in two production locations in Indonesia and a number of consumer markets abroad, namely Japan, the US, Germany, Italy and the Netherlands and estimate the percentage of price received by the coffee producers, and (b) to analyze orientation trend, integration and cointegration and their impacts on the long-term relationship among the prices in the various markets. The research was undertaken during March throughout December 2003, using time series data from 1983 through 2002. The research shows that retail prices in Japan were always higher than those of in US, Germany, Italy and the Netherlands with positive trends until 1995 and negative trend afterwards. Retail price movements in the US and the Netherlands tended to be similar, and retail prices in Germany had almost similar pattern with those of in the Netherlands, while producer prices in Indonesia were hardly fluctuate. Uncertainty, as reflected by coefficient of variations was more significant for prices received by coffee producers in Indonesia than those of prices paid by consumers in the developed countries. Aside from uncertainty factor, the percentage prices received by the coffee farmers in Indonesia (Lampung and Jawa Timur) are diminutive relative to retail prices in major importing countries. Coffee prices in Jawa Timur were only valued between 4.8 to 24.2 percent of retail prices in the importing countries and coffee prices in Lampung are much lower, only about 1.2 to 7.5 percent of retail prices in the importing countries. The coffee industry in Western Europe seemed to have strong relationship with the coffee industry in Lampung and be less strong with that of in Jawa Timur. In contrary, coffee industry in the US had strong link with that of in Jawa Timur and less strong with that of in Lampung. Despite its large size of coffee import volume from Indonesia, the market relationship between Japan and Indonesia was not that strong as generally perceived. Indonesian government should prescribe export and import policies that are required to enhance agricultural sector and agribusiness development.IndonesianSasaran pasar komoditas kopi Indonesia sampai saat ini masih mengarah ke pasar ekspor yang tersebar di berbagai kota besar di negara maju, karena konsumsi per kapita di dalam negeri sendiri masih sangat rendah dan pertumbuhannya pun juga rendah, sementara di pusat-pusat konsumen di luar negeri pertumbuhan konsumsi tampaknya cukup mantap. Namun, yang menjadi pertanyaan adalah apakah dua simpul pasar kopi ini terintegrasi dan apakah harga di pusat produksi kopi di Indonesia juga terintegrasi? Untuk merancang langkah-langkah pemberdayaan dan pengelolaan produksi petani kopi, diperlukan informasi dan data hubungan saling pengaruh dan integrasi antara pasar produsen dan konsumen ini. Makalah ini ditujukan untuk mengevaluasi perkembangan dan keragaman harga di dua lokasi produsen di Indonesia dan beberapa lokasi konsumen di luar negeri, menganalisis perubahan nilai tukar dolar Amerika Serikat (AS), serta kecenderungan orientasi dan dampaknya dalam menuju hubungan sesamanya dalam jangka panjang. Penelitian dilakukan pada bulan Maret sampai dengan Desember 2003, menggunakan data sekunder deret waktu tahun 1983 sampai dengan 2002. Penelitian menunjukkan harga eceran di Jepang selalu lebih tinggi daripada harga-harga di negara konsumen seperti AS, Jerman, Italia dan Belanda dan tren perkembangan harga cenderung positif sampai dengan tahun 1995 dan negatif sesudahnya. Harga eceran di AS dan di Belanda cenderung mempunyai pola yang sama, sedangkan harga eceran di Jerman mempunyai pola yang hampir sama dengan di Belanda dan harga produsen di Indonesia terlihat bergerak mendatar. Ketidakpastian, seperti ditunjukkan oleh koefisien keragaman lebih nyata pada harga yang diterima produsen kopi di Indonesia dibanding para konsumen di negara-negara maju. Selain faktor ketidakpastian, harga kopi yang diterima petani kopi Indonesia (Lampung dan Jawa Timur) sangat kecil jika dibandingkan dengan harga eceran di negara-negara pengimpor utama. Harga kopi di Jawa Timur hanya bernilai sekitar 4,8-24,2 persen dari harga eceran di negara konsumen dan bagi petani produsen di Lampung persentase yang diterima jauh lebih rendah, yakni hanya bernilai sekitar 1,2-7,5 persen. Industri kopi di Eropa Barat berhubungan erat dengan industri kopi di Lampung dan kurang erat dengan industri kopi di Jawa Timur. Sebaliknya, industri kopi di Amerika Serikat berhubungan erat dengan industri kopi di Jawa Timur dan kurang dengan industri kopi di Lampung. Perubahan nilai tukar dolar AS dalam jangka pendek memberikan perubahan pada harga-harga kopi di Jawa Timur lebih rendah daripada harga kopi di Lampung. Meskipun Jepang mengimpor kopi dalam jumlah besar dari Indonesia, hubungan kedua pasar kopi ini tidaklah terlalu kuat seperti diprakirakan. Seperti halnya di negara-negara lain, pemerintah seyogianya mempunyai kebijakan ekspor dan impor yang mendukung pengembangan sektor pertanian dan agribisnis yang tidak merugikan negara.